Nirmal Sengupta, Destitutes and Development. A Study of the Bauri Community in the Bokaro Region, concept Publishing Co. Nueva Delhi, 1979, 123 pp. - Devalle, Susana B. C. (Estudios de Asia y África, 1981)
-